A Real-Time LPG Leakage Detection System Based on ESP32 with Alerts via Buzzer and Telegram - Ellya Khahar, Ilham; Affandi, Fitran; Fachrezi, Dhimas (Indonesian Journal of Electrical Engineering and Electronics, 2024)
LPG gas leakage poses a serious threat that can lead to fires, explosions, and casualties if not detected early. This research designed a gas leakage detection system based on the ESP32 microcontroller using an MQ-2 sensor to detect LPG gas concentrations, a buzzer for local alerts, and remote notifications via the Telegram application. When the gas concentration exceeds the threshold, the system triggers a red LED as a visual indicator, activates a buzzer for an audible alarm, and sends real-time notifications to users through Telegram. Testing results demonstrate that the system has a fast response time of 3-5 seconds, with high accuracy in detecting gas leaks and sending notifications. With the combination of local and remote alerts, this system is proven to be effective and reliable in enhancing household safety against the risk of LPG gas leakage.